Work Commitment As An Intervening In Disaster Management Performance - Len, Yullina Eliza; Andria, Yass; Muslim, Irwan; Putri, Anne (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2024)
This study attempted to determine the effect of job competence and Compensation on performance for fifty employees of the Padang City Regional Disaster Management Agency, with work commitment serving as an intervening variable. The general population is given questionnaires to complete in order to gather information for route analysis and hypothesis testing. The study's conclusion demonstrates the significant relationships between work commitment and performance, work competence and work commitment, compensation and work commitment, and work commitment as an intervening variable and work commitment. The Implementing Unit of the Padang City Regional Disaster Management Agency's pay and performance are impacted by work and performance as well as work commitment. It is advised that future policy makers target responders with policies in the areas of job competence, compensation, work commitment, and performance, granting them the right to facilities as a result of their high-caliber and productive work. Keywords: work commitment, compensation, work commitment, Performance